Dreams as Ways of Experiencing the World: Artistic Drive and the Game of Reality (KULT_online, 2016)
Stefanie Kreuzer’s Traum und Erzählen in Literatur, Film und Kunst draws up a typology of dream-like storytelling by means of an intermedial comparison. On the basis of results offered by fictional theory and experimental dream research, she analyses literary texts, artwork, and movies in a systematic manner, aiming at characterizing dream-like storytelling. The specifics of each media type, as well as the fact that dreams and art are similar in many ways, come to light. There is no unmediated access to the subjective dream experience – nevertheless, fantasy worlds created by art can offer us valuable insight into the functioning of this extremely complex phenomenon: dreaming.